2016
DOI: 10.1007/s12663-016-0944-0
|View full text |Cite
|
Sign up to set email alerts
|

Single Injection Technique Prolotherapy for Hypermobility Disorders of TMJ Using 25 % Dextrose: A Clinical Study

Abstract: Hence the use of 25 % dextrose as a proliferant to treat hypermobilty disorders of the TMJ is recommended by us as a first line treatment option as it is safe, economical and an easy procedure associated with minimal morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 11 publications
(11 reference statements)
1
21
0
Order By: Relevance
“…27,28 Pericapsular fibrosis, after pericapsular injection around the TMJ, has been suggested by pre-and post treatment magnetic resonance imaging data. 23 Although proliferation is potentially helpful in conditions associated with degenerative extra-and intra-articular tissues, it may not be the primary mechanism of change in the present study. We selected an intraarticular protocol to avoid such potential effects, which could further limit the range of motion associated with mouth opening.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…27,28 Pericapsular fibrosis, after pericapsular injection around the TMJ, has been suggested by pre-and post treatment magnetic resonance imaging data. 23 Although proliferation is potentially helpful in conditions associated with degenerative extra-and intra-articular tissues, it may not be the primary mechanism of change in the present study. We selected an intraarticular protocol to avoid such potential effects, which could further limit the range of motion associated with mouth opening.…”
Section: Discussionmentioning
confidence: 83%
“…The direction and scale of these results are generally consistent with those of other reports of DPT for TMD and other musculoskeletal pain conditions. 11,20 One retrospective case series, 21 3 prospective case series, 14,22,23 and 2 RCTs 12,24 have reported favorable clinical outcomes of DPT for TMD, measured as a marked subjective reduction in episodes of painful subluxation. However, only 1 prospective case series and 1 RCT used a quantifiable pain measure (visual analog scale or NRS) as well as a measure of MIO (in millimeters), pre-and posttreatment.…”
Section: Discussionmentioning
confidence: 99%
“…MMO did not show any statistical significant reduction in their study. Majumdar et al reported an overall success rate of 91.3% in a sample of 23 patients after a mean follow‐up period of 13.9 months. They tried to limit the number of dextrose injections, but only seven patients (30.4%) were successfully managed by a single injection while two injections were required in 8 (34.7%) and three injections were required in six patients (26.1%) for managing hypermobility.…”
Section: Discussionmentioning
confidence: 98%
“…Pathogenesis of TMJ hypermobility is commonly associated with trauma, abnormal chewing movements, poor development of the articular fossa, weakness or laxity of the TMJ ligament and joint capsule, and excessive activity of the lateral pterygoid and infrahyoid muscles due to drugs such as phenothiazine or diseases characterised with general joint laxity (Ehlers‐Danlos syndrome, Marfan syndrome and juvenile rheumatoid arthritis) …”
Section: Introductionmentioning
confidence: 99%
“…Except for the duration of complaints, the subjects' characteristics would match with most of the reported publications. In my study, the duration of symptoms was maximumally 48 month (Mean of 24 m ± 11.4) while patients in other studies reported longer period of symptoms[17,22,23]. In the current study, patients reported a pain intensity that ranged between 5-10 on visual analogue scale.…”
mentioning
confidence: 40%